Recommendations for buprenorphine and methadone therapy in opioid use disorder: a European consensus. (12th December 2017) - Dematteis, Maurice; Auriacombe, Marc; D'Agnone, Oscar; Somaini, Lorenzo; Szerman, Néstor; Littlewood, Richard; Alam, Farrukh; Alho, Hannu; Benyamina, Amine; Bobes, Julio; Daulouede, Jean Pierre; Leonardi, Claudio; et al.
ABSTRACT: Introduction : Management of patients with opioid use disorder (OUD) commonly includes opioid agonist therapy (OAT) as a part of an integrated treatment plan. These interventions are associated with proven benefits to the individual and society. Areas covered : The use of methadone and buprenorphine within an integrated treatment plan in the management of patients with OUD: this work provides consensus recommendation on pharmacotherapy in OUD to assist clinicians with practical decision making in this field. Expert opinion : Pharmacotherapy is recommended as part of an integrated OUD treatment approach with psychosocial interventions, with the goal of reducing risks of illicit opioid use, overdose mortality, infection with HIV or HCV, improving health, psychological and social outcomes. Access to OAT should be prioritised in the treatment of OUD. Treatment choices in OUD pharmacotherapy should be based on the needs of the individual and characteristics of medications. Recommendations for choices of OAT are based on clinical efficacy, safety, patient preference, side effects, pharmacological interactions, quality of life, dose titration potential and outcomes (control craving, ongoing opioids consumption or other drugs, and potentially psychiatric comorbidities). Special groups, pregnant women, prisoners, patients with mental health problems have specific needs which must be addressed with expert input.